Avenanthramide C Suppresses Matrix Metalloproteinase-9 Expression and Migration Through the MAPK/NF- κB Signaling Pathway in TNF-α-Activated HASMC Cells - Park, Junyoung; Choi, Hyunju; Abekura, Fukushi; Lim, Hak‐Seong; Im, Jong‐Hwan; Yang, Woong‐Suk; Hwang, Cher‐Won; Chang, Young‐Chae; Lee, Young-Choon; Park, Nam Gyu; Kim, Cheorl-Ho (Frontiers in Pharmacology, 2021)
In oat ingredients, flavonoids and phenolic acids are known to be the most important phenolic compounds. In phenolic compounds, wide-ranging biological responses, including antioxidative, anti-inflammatory, anti-allergic, and anti-cancer properties, were reported. Avenanthramide C (Avn C), a component of the phenolic compound of oats, has been reported to be highly antioxidant and anti-inflammatory, but its role in an anti-atherosclerosis response is unknown. The aim of this research was to assess the effect of Avn C on expression of MMP-9 on TNF-α-activated human arterial smooth-muscle cells (HASMC) and signaling involved in its anti-atherosclerosis activity. HASMC cells are known to produce inflammatory cytokines involving IL-6, IL-1β, and TNF-α during arteriosclerosis activity. Avn C specifically reduced IL-6 secretion in HASMC cells. Furthermore, we investigated whether Avn C could inhibit NF-κB nuclear protein translocation. Avn C suppressed nuclear protein translocation of NF-κB in TNF-α-stimulated HASMCs. The MMP-9 enzyme activity and expression are controlled through the MAPKs signaling path during the Avn C treatment. We confirmed that it suppresses cellular migration and wound healing emerged by pathological conditions. Accordingly, Avn C inhibited the expression of MMP-9 and cell migration through the MAPK/NF‑κB signaling pathway in TNF-α-activated HASMC. Therefore, Avn C can be identified and serve as disease prevention material and remedy for atherosclerosis.